Diversidad comparativa de primates en aguajales de las cuencas de los ríos Marañon y Ucayali, Loreto - Perú - Salas Cruz, Frithman (2023)
In order to determine the diversity and densities of primates, an investigation was carried out in aguajales de Marañón and Ucayali, from February to September 2019. The information was increased using the linear transect method with a length of 1 km, located in dense and mixed aguajales. In both basins, 228 km were covered, where a total of 14 species were recorded, grouped into 4 families and 8 genera, with Cebidae and Pitheciidae being among the most abundant with 4 and 5 species. At the basin level, 10 species were reported in the Marañón basin and 8 in the Ucayali basin. In the dense aguajales 08 species were recorded, and in the mixed aguajales. The dominance in the aguajales of the Marañón basin turned out to be homogeneous, while the Ucayali basin, Saimiri Cassiquiarensis, was the most dominant species in the mixed aguajales. The highest densities corresponded to S. cassiquiarensis with 41.89 Ind/Km2, followed by S. illigeri 11.84 Ind/Km2 and Sapajus macrocephalus with 11.62 Ind/Km2; and the lowest densities corresponded to P. discolor with 0.15 Ind/Km2, Saguinus lagonotus .0.29 Ind/Km2, Pithecia isabela 0.29 Ind/Km2, L. lagotricha 0.38 Ind/Km2, and P. napensis 0.66 Ind/Km2. It is concluded that the population densities of large primates were very low, due to overhunting and deforestation of their habitats, so it is important to develop primate conservation mechanisms, taking into account the local participation present in this part of the Peruvian Amazone